AGROWISATA KELAPA SAWIT DI RIAU - Sarbini, Sarbini; Khadela, Pasa Nur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2015)
The purpose of this study is to find out how to cultivate oil palm in Indonesia, so it could become a tourist destination that gives welfare to the surrounding community and the Indonesian community in the development of oil palm plantations is also supported by the geographical position, topograsif, climate, hydrology, and natural conditions suitable for planting oil palm. Agrotourism is a special type of tourism that makes agricultural crops, livestock, farm as an attraction for tourists. According R.S. Damardjati (2006) Agro is a tourist attraction visits the farm with agricultural or plantation areas that are distinctive, which has been developed such that the various aspects related to the cultivated plant species has led to motivation and attraction for tourists who visit it. Keywords: Agrotourism, Attraction, Palm,Indonesia,climate,and hydrology